One-pot biosynthesis of N-acetylneuraminic acid from chitin via combination of chitin-degrading enzymes, N-acetylglucosamine-2-epimerase, and N-neuraminic acid aldolase - Liu, Quanzhen; Wei, Guoguang; Yang, Pengfan; Wang, Chengyong; Chen, Kequan; Ouyang, Pingkai; Zhang, Alei (Frontiers in Microbiology, 2023)
N-acetylneuraminic acid (Neu5Ac) possesses the ability to promote mental health and enhance immunity and is widely used in both medicine and food fields as a supplement. Enzymatic production of Neu5Ac using N-acetyl-D-glucosamine (GlcNAc) as substrate was significant. However, the high-cost GlcNAc limited its development. In this study, an in vitro multi-enzyme catalysis was built to produce Neu5Ac using affordable chitin as substrate. Firstly, exochitinase SmChiA from Serratia proteamaculans and N-acetylglucosaminosidase CmNAGase from Chitinolyticbacter meiyuanensis SYBC-H1 were screened and combined to produce GlcNAc, effectively. Then, the chitinase was cascaded with N-acetylglucosamine-2-epimerase (AGE) and N-neuraminic acid aldolase (NanA) to produce Neu5Ac; the optimal conditions of the multi-enzyme catalysis system were 37℃ and pH 8.5, the ratio of AGE to NanA (1:4) and addition of pyruvate (70 mM), respectively. Finally, 9.2 g/L Neu5Ac could be obtained from 20 g/L chitin within 24 h along with two supplementations with pyruvate. This work will lay a good foundation for the production of Neu5Ac from cheap chitin resources.